New findings in ATP supply in rod outer segments: Insights for retinopathies. (18th June 2013) - Calzia, Daniela; Barabino, Stefano; Bianchini, Paolo; Garbarino, Greta; Oneto, Michele; Caicci, Federico; Diaspro, Alberto; Tacchetti, Carlo; Manni, Lucia; Candiani, Simona; Ravera, Silvia; Morelli, Alessandro; et al.
Abstract : The present study con‐firms the presence of an extra‐mitochon‐drial oxidative phosphorylation in rod OS. This, by absorbing both light and oxygen, would produce the necessary ATP for phototransduction. The presented data may shed light on the pathogenesis of many retinal degenerative diseases, such as age‐related macular degeneration, diabetic retinopathy and retinopathy of prematurity, where oxidative stress plays a pivotal role as well as on the efficacy of many dietary supplements presently applied. Abstract : Background Information: The rod outer segment (OS) is the specialised organelle where phototransduction takes place. Our previous proteomic and biochemical analyses on purified rod disks showed the functional expression of the respiratory chain complexes I–IV and F1 Fo ‐ATP synthase in OS disks, as well as active soluble tricarboxylic acid cycle enzymes. Here, we focussed our study on the whole OS that contains the cytosol and plasma membrane and disks as native flattened saccules, unlike spherical osmotically intact disks. Results: OS were purified from bovine retinas and characterised for purity. Oximetry, ATP synthesis and cytochrome c oxidase (COX) assays were performed. The presence of COX and F1 Fo ‐ATP synthase (ATP synthase) was assessed by semi‐quantitative Western blotting, immunofluorescence or confocal laser scanning microscopy on whole bovine retinas and bovine retinal sections and by immunogold transmission electron microscopy (TEM) of purified OS or bovine retinal sections. Both ATP synthase and COX are catalytically active in OS. These are able to consume oxygen (O2 ) in the presence of pyruvate and malate. CLSM analyses showed that rhodopsin autofluorescence and MitoTracker Deep Red 633 fluorescence co‐localise on rod OS. Data are confirmed by co‐localisation studies of ATP synthase with Rh in rod OS by immunofluorescence and TEM in bovine retinal sections. Conclusions: Our data confirm the expression and activity of COX and ATP synthase in OS, suggestive of the presence of an extra‐mitochondrial oxidative phosphorylation in rod OS, meant to supply ATP for the visual transduction. In this respect, the membrane rich OS environment would be meant to absorb both light and O2 . The ability of OS to manipulate O2 may shed light on the pathogenesis of many retinal degenerative diseases ascribed to oxidative stress, as well as on the efficacy of the treatment with dietary supplements, presently utilised as supporting therapies.